EFEKTIVITAS LATIHAN EKSENTRIK PADA LATERAL EPIKONDILITIS: SUATU TINJAUAN PUSTAKA - Muhammad Rilo Pambudi; Hijr Ismail Yusriadi; Nuryani Sidarta; Mitchel Mitchel; Karina Sylvana Gani; Erica Kholinne (Jurnal Akta Trimedika, 2026)
Lateral epicondylitis is a common musculoskeletal disorder of the upper extremity characterized by lateral elbow pain resulting from degenerative tendinopathy, primarily involving the extensor carpi radialis brevis tendon due to repetitive mechanical loading. This condition frequently affects individuals of working age and may lead to functional limitations and reduced quality of life. Conservative management is considered the first-line treatment for LE, particularly in cases without significant tendon rupture. Among conservative approaches, physiotherapy plays a central role, with eccentric exercise widely recognized as a key therapeutic component. Eccentric exercise applies controlled mechanical loading to the tendon, promoting structural adaptation, collagen remodeling, and improved tendon load tolerance. Evidence from clinical trials and systematic reviews indicates that eccentric exercise is effective in reducing pain, improving grip strength, and enhancing upper limb function in patients with LE. Clinical improvement is commonly observed within 4–6 weeks of intervention, with more stable and sustained outcomes reported after 8–12 weeks of consistent training. Eccentric exercise appears to be most effective in patients with mild to moderate LE (Grade I–II), where the tendon retains adequate adaptive capacity. In severe cases (Grade III) characterized by extensive tendon damage or persistent symptoms, eccentric exercise alone may be insufficient and should be combined with additional therapeutic modalities or advanced interventions. Overall, conservative physiotherapy with an emphasis on eccentric exercise is an effective, safe, and recommended primary intervention for the management of mild to moderate lateral epicondylitis.